Pelatihan Pembelajaran Seni Musik sebagai Sarana Literasi Budaya untuk Guru Sekolah Dasar - Desyandri Desyandri; Zuryanty Zuryanty; Mansurdin Mansurdin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The background of this service is the lack of knowledge and skills of teachers in making music as a cultural literacy for elementary school teachers. The purpose of this service is to improve the experience and skills of primary school teachers in learning the art of music as a means of cultural literacy for elementary school teachers. This service method uses the seminar method and hands-on training. The results of the dedication showed an increase in the knowledge and skills of teachers in making music art learning a cultural literacy for elementary school teachers. The implications of this service can be used as a reference by teachers and education practitioners to improve the quality of art learning and its relation to cultural literacy.